Augmented Reality-Based Flashcard Media Development with Canva's Assistance to Improve Social Science Learning Outcomes on Ethnic Diversity in Indonesia - Bibit Sri Rahayu; Hikmah Eva Trisnantari; M. Abdul Roziq Asrori (STKIP Taman Siswa Bima, 2025)
The topic of ethnic diversity in Indonesia, which is abstract and contains abundant factual information, requires media that can present content visually, interactively, and engagingly. Digital technology such as Augmented Reality (AR) in instructional media has the potential to bridge this gap by offering a more immersive and contextual learning experience. This study aimed to develop innovative learning media in the form of AR-based flashcards designed with the assistance of the Canva application to improve student learning outcomes in Social Studies material on ethnic diversity in Indonesia. The research employed the ADDIE development model. Data collection techniques included observation, interviews, validation by material and media experts, as well as pretests and posttests. Expert validation indicated that the AR-based flashcard media assisted by Canva was highly feasible for instructional use, with an average feasibility score of 92. A paired sample t-test on pretest and posttest scores showed a significant difference (Sig. 0.000 < 0.05) with an N-Gain value of 0.71 (high category), indicating a substantial improvement in learning outcomes in both cognitive aspects and active participation. The flashcards contained visual information on ethnic names, traditional clothing, traditional houses, regional languages, and unique facts, presented interactively through QR codes and the AR application. Thus, this medium proved effective in delivering cultural diversity material in an engaging, enjoyable, and easy-to-understand way, while also opening opportunities for applying digital technology to strengthen students’ understanding of diversity values.